Survey effect of energy therapy method on anxiety and incidence of cardiac Dysrhythmia inpatients under cardiac catheterization - M Zolfaghari; M Hazrati (Tehran University of Medical Sciences, 2001)
This study was conducted to determine the effect of energy therapy Method on anxiety and incidence ofcardiacdysrhythmiainpatientsundercatheterization.Thenvestigated units consisted of 68 patients that were randomly assigned into 3 groups: 26 patients in case group, 21 patients in placebo group and 21 patients in control group . The case group underwent the course of study through energy therapy method for 10-15 minutes ,one hour before catheterization. Furthemore, placebo group received mimic energy therapy within the same period of time, i. e (the method was the same as energy therapy except in this method no energy was transferred, and the procedure was unreal and mimicking). Moreover the control group received no treatment.For collection of data, the questionare and observation checklist were used. The anxiety of the patients was measured through speilberger anxiety -test, an hour before and during catheterization.The cardiac dysrhythmia and dysrhythmia during catheterization were recorded on an observation checklist.The results showed that energy therapy had a significant effect on the situational anxiety of the investigated units in case group and through energy therapy, their anxiety were reduced, (p=000)however, it had no considerable effect on the anxiety related to the characteristic of the individuals. In addition to the above, energy therapy could be effective in reducing the incidence of cardiac dysrhythmia such as: sinus tachycardia, (p=0.00005),V.T (p=0.005), PAC(p=0.001)and PVC.(p=0.01) The results also showed that energy therapy is a method reducing the anxiety of the patients in catheterization room, it could also be effective in reducing the complications such as cardiac dysrhythmia regarding to catheterization. Therefore, the investigation hypothesis was approved.